Development and Characterization of Innovative Nutraceutical Corn Jam - Ahsan, Mehak; Asif, Rida; Wasi, Nitasha; Tariq, Sana; Fawad, Summaiyah; Ejaz, Tanzila; Raza, Rashid (Journal of Research (Science), 2025)
Many fruit jams are available in the market such as strawberry, pineapple, apricot, andorange but no jam has been reported to be formulated with corn. This prompted the ideaof establishing corn based jam. This study was therefore, aimed to produce a newinnovative corn jam. Standard methods were applied for sensory analysis andphysicochemical (proximate) analysis. Among the various combinations, the newlydeveloped corn jam containing 155g corn and 93g jaggery was found to be better for itsnutritional quality and sensory evaluation. All three samples of newly prepared corn jamhave been found highly acceptable according to sensory evaluation. The pH, acidity,brix, moisture, ash, protein, fat, fiber, carbohydrates and antioxidant activity of sampleselected on the bases of organoleptic properties were found to be 3.5, 0.1%, 68.5 o,1.74%, 2.22%, 0.21%, 2.0%, 0.01%, 65.99% and 7.89% respectively. On the sensorypoint of view, all three samples of the presently developed corn based jam were foundhighly acceptable. Viscosity and consistency analysis showed good quality attributes ofcorn based jam. The newly developed corn based jam also has the market competentprice therefore the product is likely to gain the attraction of consumer and improves themarket trends.